Perceived organizational support, perceived supervisory support, job satisfaction and organizational commitment among employees in companies at Wesports - Bathmavathy, Ramachandran (2018)
The main objective of this study was to investigate the relationship between perceived organizational support, perceived supervisory support, job satisfaction and organizational commitment among employees in Malaysia shipping industry. Perceived organizational support, perceived supervisory support, job satisfaction are independent variables and organizational commitment is the dependent variables. This study used convenience sampling. 200 questionnaires were distributed in Ocean Alliance or west ports shipping organization in Klang valley and 182 questionnaires were returned. Questionnaire was used to collect the data. Data were analyzed using SPSS software version 23. Analyses used such as reliability analysis, descriptive analysis, correlation analysis (Pearson Correlation Analysis) and regression analysis (Multiple Regression Analysis). The Pearson correlation analysis revealed a positive and significant relationship between Perceived organizational support, perceived supervisory support, job satisfaction and organizational commitment. The results of regression analysis showed 23% of the factor perceived organizational support, perceived supervisory support, job satisfaction in this study contributed to the organizational commitment. The regression results indicated perceived supervisory support does not indicated significant relationship with organizational commitment, whereas perceived organizational support, and job satisfaction have positive and significant relationship with organizational commitment.